Laboratory comparison of the crumb-rubber and SBS modified bitumen and hot mix asphalt - Kok, Baha Vural; Colak, Hakan (Elsevier Sci Ltd, 2011)
The use of crumb rubber (CR) recycled from waste tires using an ambient grinding process was evaluated at two stages in asphalt formulation. First, bitumen modified with crumb rubber was evaluated by rotational viscometery (RV), dynamic shear rheometry (DSR) and conventional binder tests. Hot asphalt mixtures including crumb-rubber-modified bitumen were then evaluated by determining the permanent and fatigue characteristics and stiffness moduli of control and modified mixtures. The properties of the crumb-rubber-modified bitumen and asphalt mixtures were compared to different contents of styrene-butadiene-styrene (SBS) modified-bitumen and asphalt mixtures. The tests showed that to achieve the same performance, as with SBS-modification, the CR-content must be used at much higher than SBS. 8%-CR modification was determined as the most suitable content according to both binder and mixture tests. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Crumb rubber; SBS; Modification; Rheology; Mechanical properties